La mediación lectora en contextos internacionales. Los casos de Chile, Polonia y Portugal - Christian Alejandro Arenas Delgado; Herminda Otero Doval; Cecylia Tatoj (Investigaciones Sobre Lectura)
The present article, part of the project “Reading habits in international contexts of secondary school students. A study of educational practices for the promotion of reading” (PR2018057), reports the results of an exploratory-observational scope research extracted from that context. The main objective is to evidence research hypotheses on the training needs of reading teachers. It investigates some areas of the reading habits of Chilean, Polish and Portuguese adolescents who are in transition between primary and secondary school. There are common and divergent patterns in the answers to a questionnaire that delves into motivational and teaching aspects linked to reading education: leisure reading habits, the provenance of the books students read and the use of libraries, the hierarchization of the importance of reading, the strategies of teachers who train reading skills and also the initiatives to promote reading in schools, and their participation. In the light of results obtained, paths of educational and didactic research are proposed that allow to add value to the role of teachers as mediators of reading in the three national contexts that are part of the analysis.